Online Verbal Argumentative Interaction (OVAI) in an Online Science Class During the Covid-19 Pandemic - Archila, Pablo Antonio; Truscott de Mejía, Anne-Marie; Restrepo, Silvia (Online Learning, 2022)
As we begin the third decade of the twenty-first century, argument and debate are not habitual practices of university science education. This can be explained by the hegemony of instructor-centered traditional approaches in many of these practices. The Covid-19 pandemic has not only pushed university education online but also seems to provide an unforeseen opportunity to develop deep educational transformations. Here, we report on the case of a university online science course that, because of the Covid-19 crisis, used online verbal argumentative interaction (OVAI) to provide students with explicit opportunities to co-construct reason-based and/or evidence-based arguments and counterarguments in an undergraduate-centered science learning environment. The written arguments and counterarguments co-constructed by forty students (20 females and 20 males, 19–24 years old) during OVAI sessions were analyzed to determine their quality. Also, students’ opinions about the use of OVAI in times of Covid-19 were documented. The results indicate that the students co-constructed high-quality arguments and counterarguments in the OVAI sessions. Most importantly, participants showed positive impressions about the use of OVAI in university online science education. The outcomes carry important educational implications considering the growing university online science courses in the pandemic and post-pandemic eras.